A wideband spectrum sensing approach based on sub-band matching selection - Yuzhi YAN; Youming LI; Mingchen YU; Caimei FU; Guili ZHOU (Dianxin kexue)
Wideband spectrum sensing technology based on compressed sensing can effectively reduce the high sampling rate and the complexity of spectrum sensing.During the sensing process,in order to enhance the reconstruction performance of the spectrum signal,a modified OMP sub-band matching selection algorithm for wideband spectrum reconstruction based on the prior knowledge of boundary information and the block sparse characteristics of wideband frequency signal was proposed.This method can reduce the number of iterations in spectrum reconstruction with OMP algorithm and enhance stability of spectrum reconstruction.Simulation results show that the proposed method can not only improve the accuracy of spectrum reconstruction,but also effectively shorten spectrum sensing timeand achieve better wideband spectrum sensing performance.